2019
DOI: 10.3390/su11133532
|View full text |Cite
|
Sign up to set email alerts
|

Approach Methodology for Comprehensive Assessing the Public Passenger Transport Timetable Performances at a Regional Scale

Abstract: The paper is focused on the issue of assessing the quality of transport connectivity on a predesignated transport network in regular public passenger transport at a regional scale. Comprehensively, using the defined key qualitative indicators, it assesses the performance of passenger transport timetables, in both ways of ex ante, as well as ex post. Existing methodologies in a given issue have only dealt with a partial assessment of the transport connectivity quality on specific transport network. However, unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Achieving optimum traffic flow over time requires infrastructure managers to use capacity management and marketing tools to allocate train paths to reflect traffic flow over time so as to get as close as possible to the defined optimal value. The first priority is the technical conditions for access to infrastructure and the second is the infrastructure access clearing system [2,10,16,25,[28][29][30][31].…”
Section: New Approaches To Capacity Managementmentioning
confidence: 99%
“…Achieving optimum traffic flow over time requires infrastructure managers to use capacity management and marketing tools to allocate train paths to reflect traffic flow over time so as to get as close as possible to the defined optimal value. The first priority is the technical conditions for access to infrastructure and the second is the infrastructure access clearing system [2,10,16,25,[28][29][30][31].…”
Section: New Approaches To Capacity Managementmentioning
confidence: 99%
“…To evaluate the current state of passenger transport on these lines we looked at the number of regional (R) and interregional (IR) trains on each line in a normal weekday (considering both directions) [20]. The cost of one journey was defined for regional trains as the fare for one full 2nd…”
Section: Railway Lines Around Bucharestmentioning
confidence: 99%
“…So, as a result of a survey among passengers of sea transport by the authors of the work [6], it is revealed that the development of linear passenger transportation is hindered due to the low quality of transport services and high cost. In [7,8] criteria and methodology for assessing the quality of transport services are defined. And in the work [9], a method is proposed for improving the quality of transport services by managing financial flows that ensure the functioning of the transport services market.…”
Section: Shipping Companymentioning
confidence: 99%